2010
DOI: 10.1007/s10557-010-6241-0
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic Plaque Regression: Fact or Fiction?

Abstract: Coronary artery disease is the major cause of death in the western world. The formation and rapid progression of atheromatous plaques can lead to serious cardiovascular events in patients with atherosclerosis. The better understanding, in recent years, of the mechanisms leading to atheromatous plaque growth and disruption and the availability of powerful HMG CoA-reductase inhibitors (statins) has permitted the consideration of plaque regression as a realistic therapeutic goal. This article reviews the existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Therefore loss to follow-up, in combination with the relatively small sample size, might potentially contribute to the null associations in our study. Finally, after the first ultrasound examination of carotid atherosclerosis, it was possible that some participants might have taken medications (eg, statins) that were able to reduce progression of atherosclerosis 48. We did not have information on medication use during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore loss to follow-up, in combination with the relatively small sample size, might potentially contribute to the null associations in our study. Finally, after the first ultrasound examination of carotid atherosclerosis, it was possible that some participants might have taken medications (eg, statins) that were able to reduce progression of atherosclerosis 48. We did not have information on medication use during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown in these studies that early initiation of ERT may prevent arterial vasculopathy associated with MPS-I, and have reported elsewhere that the same is true for other refractory tissues such as the atrioventricular valve 27. Whether longer term therapy initiated in older animals would eventually result in complete remodeling and regression of these plaques, as suggested for atherosclerosis,42 remains to be determined. Further investigation of the pathogenic role abnormal GAG accumulation plays in altering the normal cell-cell, cell-matrix interactions in MPS-I (and other storage diseases) is warranted in order to develop adjunct therapies that complement use of recombinant IdU.…”
Section: Discussionmentioning
confidence: 99%
“…This detection is line with recent development which reported that the disruption and loss of villi or overlaying mucosa play an important function in pathogenesis of the small intestine resulting into accumulation of cholesterol (cholesterolemia) in the blood and complicated atherosclerosis (Shanmugma et al., 2010). Additionally, the spleen synthesizes antibodies in its white pulp, destroys old, and damaged cells.…”
Section: Resultsmentioning
confidence: 99%